Mechanisms Involved in the Formation of Biocompatible Lipid Polymeric Hollow Patchy Particles - Rasheed, Nashaat (Langmuir : the ACS journal of surfaces and colloids, 2015)
Patchy polymeric particles have anisotropic surface domains that can be remarkably useful in diverse medical and industrial fields because of their ability to simultaneously present two different surface chemistries on the same construct. In this article, we report the mechanisms involved in the formation of novel lipid-polymeric hollow patchy particles during their synthesis. By cross-sectioning the patchy particles, we found that a phase segregation phenomenon occurs between the core, shell, and patch. Importantly, we found that the shear stress that the polymer blend undergoes during the particle synthesis is the most important parameter for the formation of these patchy particles. In addition, we found that the interplay of solvent-solvent, polymer-solvent, and polymer-polymer-solvent interactions generates particles with different surface morphologies. Understanding the mechanisms involved in the formation of patchy particles allows us to have a better control on their physicochemical properties. Therefore, these fundamental studies are critical to achieve batch control and scalability, which are essential aspects that must be addressed in any type of particle synthesis to be safely used in medicine